Comparison between bacampicillin and amoxycillin in treating genital and extragenital infection with Neisseria gonorrhoeae and pharyngeal infection with Neisseria meningitidis. Issue 6 (December 1984) - Edwards, L D; Gartner, T
Abstract : Sixty three patients presumed to have genital gonorrhoea who gave histories of extragenital sexual practices were randomly treated with amoxycillin 3 g or bacampicillin 4.8 g (equivalent to 3.5 g ampicillin) with probenecid 1 g to compare the efficacy of the drugs in treating gonorrhoea at all sites. Three patients were initially culture negative, and seven failed to return for follow up. Twenty seven of 28 patients receiving bacampicillin and all 25 receiving amoxycillin gave negative genital cultures for Neisseria gonorrhoeae five to nine days after treatment. Twenty two of 60 patients had extragenital gonorrhoea. One failed to return, but all eight who had received amoxycillin and 12 of 13 who had received bacampicillin gave negative pharyngeal and anorectal cultures after treatment. N meningitidis was isolated from the pharynx in 17 of 60 patients on initial attendance. Three of 14 were still colonised with the meningococcus after treatment. Two of 32 patients receiving amoxycillin and 12 of 31 receiving bacampicillin reported experiencing gastrointestinal side effects.